Allergic and non-allergic asthma in children hospitalized in the University Children’s Hospital in Lublin in 2016-2020 - Szuba, Joanna; Wawryk-Gawda, Ewelina; Brzuszkiewicz, Kinga; Urbanska, Katarzyna (Current Issues in Pharmacy and Medical Sciences, 2022)
Introduction. Bronchial asthma is a common disease characterized by chronic inflammation of the airways. Paediatric asthma is still a current problem and children with exacerbation frequently are hospitalized. The aim of the study was to determine the prevalence of allergic and non-allergic asthma in children hospitalized at the Department of Paediatric Pulmonology and Rheumatology of the University Children’s Hospital in Lublin in 2016-2020, and to analyze the most common allergens associated with allergic asthma.Materials and methods. The study group consisted of 667 patients, aged 6 to 215 months (average 64 months). The data collected for this retrospective study includes: gender, age, month, quarter of year, and year of hospitalization, type of asthma and type of allergens. Results. We observed a decrease of hospitalization in the analyzed years: in 2016 – 160 children, and in 2020 – 74. Children with allergic asthma (375 children) were more frequently hospitalized than patients with non-allergic asthma, and we found correlations between age and type of asthma and between age and type of allergy. Non-allergic asthma was observed in the youngest children, while in older children, allergic-asthma dominated. We also observed significant differences in children’s hospitalization depending on the season of the year. The most frequent allergen causing asthma was house dust mites.Conclusions. The incidence of hospitalizations caused by asthma exacerbation is declining. Among the youngest population, exacerbations of asthma related to respiratory tract infection predominate, while in the older, allergy to inhalation allergens is the main cause.